Ice formation on nitric acid‐coated dust particles: Laboratory and modeling studies. Issue 15 (4th August 2015) - Kulkarni, Gourihar; Zhang, Kai; Zhao, Chun; Nandasiri, Manjula; Shutthanandan, Vaithiyalingam; Liu, Xiaohong; Fast, Jerome; Berg, Larry
Abstract: Changes in the ice nucleation characteristics of atmospherically relevant mineral dust particles caused by a coating of nitric acid are not well understood. Further, the atmospheric implications of dust coatings on ice‐cloud properties under different assumptions of primary ice nucleation mechanisms are unknown. We investigated the ice nucleation ability of Arizona Test Dust, illite, K‐feldspar, and quartz as a function of temperature (−25°C to −30°C) and relative humidity with respect to water (75% to 110%). The particles (bare or nitric acid coated) were size selected at 250 nm, and the fraction of particles nucleating ice at various temperature and saturation conditions was determined. All of the dust species nucleated ice at subsaturated conditions, although the coated particles (except quartz) showed a reduction in their ice nucleation ability relative to bare particles. However, at supersaturated conditions, bare and coated particles had nearly equivalent ice nucleation characteristics. The results of a single‐column model showed that simulated ice crystal number concentrations are mostly dependent upon the coated particle fraction, primary ice nucleation mechanisms, and competition among ice nucleation mechanisms to nucleate ice. In general, coatings were observed to modify ice‐cloud properties, and the complexity of ice‐cloud and mixed‐phase‐cloud evolution when different primary ice nucleation mechanisms compete for fixed water vapor budgets was supported. Key Points: IN properties of bare and nitric acid‐coated dust particles are investigated IN properties of coated particles were reduced at subsaturated conditions Model cloud properties were sensitive to ice mechanisms and dust aging fraction